PEMODELAN RISIKO EPIDEMI PADA BUDIDAYA MASSAL MAGOT (HERMETIA ILLUCENS) MENGGUNAKAN MODEL SIR - Anggriani, Nita; Handayani, Lilis; Ermita, Ermita (MUST: Journal of Mathematics Education, Science and Technology, 2025)
Hermetia illucens, or the Black Soldier Fly  (BSF) maggot, is widely cultivated due to its ability to convert organic waste into economically valuable biomass; however, high colony density increases the risk of disease transmission. This study aims to analyze infection dynamics in maggot colonies using a mathematical modeling approach based on the Susceptible–Infected–Removed (SIR) epidemiological model. A system of differential equations was formulated by incorporating transmission rate (β), recovery or isolation rate (γ), and mortality rate (μ). Simulations were conducted on an initial population of 10,000 larvae with 100 infected larvae on the first day, evaluating three control scenarios: no control, improved sanitation, and rapid quarantine. Model parameters were assumed based on insect epidemiology literature. The results show that without control, an R₀ of 3.50 leads to a rapidly spreading outbreak with a peak infection of approximately 3,600 larvae. The sanitation scenario reduces R₀ to 2.00 with a peak of around 1,500 infected larvae, whereas rapid quarantine lowers R₀ to 1.40 and results in only about 500 infected larvae with a shorter outbreak duration. These findings indicate that sanitation measures and rapid quarantine are effective in reducing outbreak risks in BSF cultivation, with rapid quarantine being the most efficient strategy. The study provides an early theoretical contribution to applying simple epidemiological modeling to support biosafety practices in the BSF industry.